Pengaruh Kualitas Pelayanan dan Promosi Terhadap Keputusan Pembelian Sepeda Motor Bekas Studi pada Showroom Sepeda Bekas di Singaraja - Febriantari, Kadek Gita; I Nyoman Sujana (Universitas Pendidikan Ganesha, 2025)
This study aims to determine (1) the effect of service quality on purchasing decisions, (2) the effect of promotion on purchasing decisions, (3) the effect of service quality and promotion on purchasing decisions. The population in this study, namely all consumers who have purchased used motorcycles totaling 676 people. The sampling technique used was Proportional Random Sampling, with a sample size of 87 respondents. The data collection method used a questionnaire and was analyzed using multiple linear regression analysis. Hypothesis testing was carried out partially using the t-test and simultaneously using the F-test processed with the help of the Statistical Package For The Social Science (SPSS) version 25 software. The results of the study showed that (1) service quality had a positive and significant effect on purchasing decisions for used motorcycles at used motorcycle showrooms in Singaraja, (2) promotion had a positive and significant effect on purchasing decisions for used motorcycles at used motorcycle showrooms in Singaraja, (3) service quality and promotion had a positive and significant effect on purchasing decisions for used motorcycles at used motorcycle showrooms in Singaraja.